When Courts Redesign Democracy: The Politics of Constitutional Adjudication in Indonesia’s Regional Election System - Sahrin Hamid (Universitas Warmadewa, 2026)
In many developing democracies, constitutional courts (Mahkamah Konstitusi: MK) have evolved beyond their traditional role as guardians of legality to become active agents in shaping the design of democratic institutions. Indonesia's Constitutional Court is increasingly exercising this transformative capacity, particularly through its interventions in the regional election system. In Indonesia, the MK is increasingly exercising this transformative capacity, particularly through its intervention in the regional election system. This article investigates how the 2024 MK ruling (Decision No. 60/PUU-XXII/2024), which removed the electoral threshold for regional head candidacy, has recalibrated the interaction between political parties and state institutions in Indonesian democracy. Using a framework of political jurisprudence combined with concepts from institutional change theory, this study places the MK's decision within a broader debate on judicial activism, party system adaptation, and constitutional politics in electoral design. This analysis suggests that the MK’s intervention not only liberalized the selection of local candidates but also reshaped coalition incentives, as interpreted through an analysis of judicial reasoning and post-decision party strategies. By conceptualizing constitutional adjudication as a mode of redesigning democracy, this study advances a nuanced understanding of how judicial institutions in democracies act as de facto architects of political reform. It contributes theoretically to comparative discussions on judicial power and institutional evolution, and empirically to studies on the ongoing consolidation of democracy in Indonesia.